Contribuição dos isótopos ambientais e hidroquímica para o conhecimento das águas subterrâneas na Bacia de Lavras da Mangabeira - Granjeiro, Michel Lopes (2008)
Groundwaters from two sub-basins, one of the Riacho of Rosário and the other of the Riacho do Meio, in the Sedimentary Basin of Lavras da Mangabeira were studied using measurements of the environmental isotopes oxygen-18, deuterium and carbon14, and hydrochemistry and bacteriological analyses. δ18O values range from -3,1 to - 0,2 ‰ and δD, from -17,9 to -3,6 ‰, indicating that the waters suffered evaporation and that recharge is probably through the respective river of each sub-basin. The waters in both sub-basins are stored in the Formations Serrote do Limoeiro and Iboperi, with those of less salt concentration in F. Iboperi. Except for the well P01, the waters have low salinity and are potable with respect to hydrochemistry. Waters of the types mixed/bicarbonate and sodium/bicarbonate prevail. Carbon-14 analyses on samples from the Riacho do Meio sub-basin revealed that these waters are not modern, but show equivalent residence times of the order of 3900years, most probably resulting from mixing of different recharge contributions. Bacteriological analyses showed that the waters are not potable due to the elevated number of coliforms and of E. Coli.